Neuropathology in Drosophila mutants with increased seizure susceptibility. - Fergestad, T.; Olson, L.; Patel, K.P.; Miller, R.; Palladino, M.J.; Ganetzky, B. (Genetics, 2008)
Genetic factors are known to contribute to seizure susceptibility, although the long-term effects of these predisposing factors on neuronal viability remain unclear. To examine the consequences of genetic factors conferring increased seizure susceptibility, we surveyed a class of Drosophila mutants that exhibit seizures and paralysis following mechanical stimulation. These bang-sensitive seizure mutants exhibit shortened life spans and age-dependent neurodegeneration. Because the increased seizure susceptibility in these mutants likely results from altered metabolism and since the Na(+)/K(+) ATPase consumes the majority of ATP in neurons, we examined the effect of ATPalpha mutations in combination with bang-sensitive mutations. We found that double mutants exhibit strikingly reduced life spans and age-dependent uncoordination and inactivity. These results emphasize the importance of proper cellular metabolism in maintaining both the activity and viability of neurons.